The Roles of Stroma-Derived Chemokine in Different Stages of Cancer Metastases - Hussain, Shahid; Peng, Bo; Cherian, Mathew; Song, Jonathan W.; Ahirwar, Dinesh K.; Ganju, Ramesh K. (Frontiers in Immunology, 2020)
The intricate interplay between malignant cells and host cellular and non-cellular components play crucial role in different stages of tumor development, progression, and metastases. Tumor and stromal cells communicate to each other through receptors such as Integrins and secretion of signaling molecules like growth factors, cytokines, chemokines and inflammatory mediators. Chemokines mediated signaling pathways have emerged as major mechanisms underlying multifaceted roles played by host cells during tumor progression. In response to tumor stimuli, host cells-derived chemokines further activates signaling cascades that support the ability of tumor cells to invade surrounding basement membrane and extra-cellular matrix. The host-derived chemokines act on endothelial cells to increase their permeability and facilitate tumor cells intravasation and extravasation. The tumor cells-host neutrophils interaction within the vasculature initiates chemokines driven recruitment of inflammatory cells that protects circulatory tumor cells from immune attack. Chemokines secreted by tumor cells and stromal immune and non-immune cells within the tumor microenvironment enter the circulation and are responsible for formation of a “pre-metastatic niche” like a “soil” in distant organs whereby circulating tumor cells “seed’ and colonize, leading to formation of metastatic foci. Given the importance of host derived chemokines in cancer progression and metastases several drugs like Mogamulizumab, Plerixafor, Repertaxin among others are part of ongoing clinical trial which target chemokines and their receptors against cancer pathogenesis. In this review, we focus on recent advances in understanding the complexity of chemokines network in tumor microenvironment, with an emphasis on chemokines secreted from host cells. We especially summarize the role of host-derived chemokines in different stages of metastases, including invasion, dissemination, migration into the vasculature, and seeding into the pre-metastatic niche. We finally provide a brief description of prospective drugs that target chemokines in different clinical trials against cancer.